Corporate financial strategy in an emerging market: Evidence from Indonesia - Erik Syawal Alghifari; Atang Hermawan; Ardi Gunardi; Agus Rahayu; Lili Adi Wibowo (Journal of Risk and Financial Management, 2022)
This paper focuses on strategic corporate financial decisions related to capital structure to increased firm value, moderated by the COVID-19 pandemic under MM theory, trade-off theory, and pecking order theory. The analytical method used is panel data analysis, with observations of 1828 non-financial companies on the Indonesia Stock Exchange from the years 2019 to 2021. The results show that there is an effect of capital structure on firm value in a positive direction, and the moderating role of the COVID-19 pandemic weakens the effect of capital structure on firm value. The findings show that capital structure only has a significant effect on firm value for the debt-dominant group, but not for the equity-dominant group. The moderating effect of the COVID-19 pandemic affects firm value for the debt-dominant group, but not for the equity-dominant group.
Keywords: 650; capital structure; emerging market; financial strategy; firm value; pandemic COVID-19